Assessment of First Aid Emergency Knowledge Among Medical Students from First Year to Final Year-A Comparative Study - Hisam, Aliya; Mashhadi, Syed Fawad; Ameer, Zainab; Khan, Affan Ahmed; Sattar, Danish; Tahir, Zeeshan; Yaqub, Pakeeza (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To assess the level of first aid knowledge among undergraduate medical students in Army Medical College, Rawalpindi. The research aimed to compare the level of medical knowledge across five years of medical training and to evaluate the effect of demographic details on the degree of first aid awareness.Study Design: The study design is cross-sectional.Place and Duration of Study: Study was conducted in Army Medical College, Rawalpindi Pakistan, from Nov 2021 to Apr2022Methodology: A preformed questionnaire was used and was divided into two groups: The first group contained two parts: i) Personal information and ii) Question about previous attendance of the first aid course. The second group contained 14 questions aimed at assessing major aspects of first-aid. The results for every year were compared. Data was entered an SPSS version 25.Results: In the study there was a marked increase in the level of first aid knowledge from first year to final year. The study also showed that those living at home had better scores than those availing university accommodation. Demographic background or receiving training in first-aid had an insignificant effect on it.Conclusion: The study discovered that the academic year had a substantial impact on knowledge levels. From first year to final year, there was a significant increase in first-aid knowledge. Every year, medical students' first-aid education should be reinforced in order to improve their skills.